Coronary artery aneurysms following drug eluting stents implantation: A retrospective analysis from series of cases at tertiary care cardiac centre over three years - Sudarshan Kumar Vijay; Dharmendra Kumar Srivastava; Bhuwan Chandra Tiwari; Mukul Misra (Heart India, 2019)
Background: Inflammation and healing after vascular injury during the procedure and other factors may be theoretically associated with a risk of coronary artery aneurysm (CAA) formation after drug eluting stent (DES) implantation. Very few studies have provided the epidemiological features and proposed causative factors of CAAs after DES implantation. Aims and Objectives: We aim to retrospectively study the incidence, morphological features and proposed causative factors of coronary artery aneurysms noted after drug eluting stent implantation at a tertiary care cardiac centre over period of three years (2015-2018). Methods: All cases of coronary artery aneurysms occurring after drug eluting stent implantation over a period of three years (2015-2018) were studied retrospectively. Incidence, morphological and clinical features of aneurysms were retrospectively analysed from case records and angiographic analysis from computerized database at our tertiary care cardiac centre. Results: Over period of three years (2015-2018) seven cases (Incidence-0.52%) of coronary artery aneurysms were noted after DES implantation with 1340 coronary angioplasty and stenting procedures done during this period for any indication. Association of diabetes and and high pressure post dilation was seen in five (71.4%) cases. A male sex and Left anterior descending artery predilection was noted and all incriminated stents were durable polymer stents. Dissection during predilatation of the lesion was seen in two (28.5%) patients. Conclusions: Coronary artery aneurysms associated with DES implantation are rare in the current era of biodegradable polymer stents. Various procedure and stent related factors are involved in its causation.